Coined by God : words and phrases that first appear in the English translations of the Bible - Malless, Stan, 1947-; McQuain, Jeff, 1955- (New York : Norton, 2003)
Lists 150 English words and phrases that originated in the Bible, including "blood money" and "salt of the Earth," in a volume complemented by meanings and sources as well as chapter and verse identifications.
Includes bibliographical references (p. [203]-205) and indexes.
Keywords: Bible. -- Versions -- History; English language -- New words; Bible -- Language, style